2017
DOI: 10.15537/smj.2017.12.21462
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of alveolar ridge splitting and autogenous onlay bone grafting to enable implant placement in patients with atrophic jaw bones

Abstract: Objective:To compare alveolar ridge splitting (ARS) and autogenous onlay bone grafting (AOBG) in atrophic jaw bones.Methods:Forty patients were included in this retrospective, parallel-group study conducted at the Istanbul Medipol University School of Dentistry, Istanbul, Turkey, between 2012-2015. The initial bone thickness was measured by cone beam computed tomography (CBCT). Patients were allocated into ARS (n=17) and AOGB (n=23) groups on the basis of ridge thickness and shape. Follow-up CBCT measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
1
17
0
1
Order By: Relevance
“…Out of the 23 studies (Table 1), there were 11 randomised controlled clinical trials [21-24, 26, 29-32, 36, 37, 39], one prospective cohort study [34,40], three retrospective cohort studies [18,20,33], and eight case series [16,17,19,25,27,28,35,38,[41][42][43], of which two research groups independently published two follow-up papers on the same study cohort [21,22,27,28], and they have been collectively grouped under one study name for this analysis. The follow-up period after ridge augmentation or implant placement was reported in all studies except two [16,35], and it ranged from 3.1 months to 10 years.…”
Section: Study Design and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 23 studies (Table 1), there were 11 randomised controlled clinical trials [21-24, 26, 29-32, 36, 37, 39], one prospective cohort study [34,40], three retrospective cohort studies [18,20,33], and eight case series [16,17,19,25,27,28,35,38,[41][42][43], of which two research groups independently published two follow-up papers on the same study cohort [21,22,27,28], and they have been collectively grouped under one study name for this analysis. The follow-up period after ridge augmentation or implant placement was reported in all studies except two [16,35], and it ranged from 3.1 months to 10 years.…”
Section: Study Design and Characteristicsmentioning
confidence: 99%
“…Two studies nursed wound dehiscence sites by recalling patients once a week for 4 weeks for professional local disinfectant application, and once a month thereafter until complete resolution [21,22]. Two studies reported management of wound dehiscences with exposed graft materials by removing the sequestered bone [16] and treating the site with a combination of an antimicrobial mouth rinse and systemic antibiotics [16,20]. Two studies reported uneventful and spontaneous healing of dehisced sites [17,24].…”
Section: Management Of Post-surgical Complicationsmentioning
confidence: 99%
“…The benefit of additional defect walls was clearly demonstrated by Cortellini et al who found that bone defect fill improved proportionally to the number of residual defect walls (20). The main advantage of this technique is a predictable amount of bone gain; rapid vascularization, leading to improved bone healing; and the expanded defect heals in a similar manner to an extraction socket (21)(22)(23). Grafting between the fractured cortical lamellae is better integrated and opening of marrow space improves vascularization and healing (24).…”
Section: Discussionmentioning
confidence: 98%
“…1 Tooth loss represents a serious and disabling condition, requiring an appropriate therapeutic intervention to obtain complete recovery that meets patient expectations. 3 Reconstructive preimplant surgery represents a valid therapeutic option 3 to restore proper alveolar morphology and create ideal conditions for an adequate implant-prosthetic rehabilitation. 2 In cases of severe jaw atrophy, the poor quality and quantity of bone tissue may compromise osseointegration of the fixture, especially in the posterior region of the jaw.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, more complex rehabilitation strategies are required. 3 Reconstructive preimplant surgery represents a valid therapeutic option 3 to restore proper alveolar morphology and create ideal conditions for an adequate implant-prosthetic rehabilitation. 4,5 Calvarial autogenous bone is considered the gold standard treatment for its excellent osteogenic, osteoconductive, and osteoinductive properties and its resistance to bone resorption.…”
Section: Introductionmentioning
confidence: 99%